Уточнення параметрів регресійної залежності між функціями основних розмірів шестерень масляних насосів транспортних двигунів внутрішнього згоряння - Стефановський, Олексій Борисович; Стефановский, Алексей Борисович; Stefanovskyi, Oleksii; Болтянський, Олег Володимирович; Болтянский, Олег Владимирович; Boltianskyi, Oleh (My University, 2021)
UK: На основі аналізу опублікованих відомостей про шестерінчасті масляні насоси транспортних двигунів внутрішнього згоряння запропоновані уточнені варіанти регресійної залежності відношення ширини і зовнішнього діаметра шестерень такого насоса (з зовнішнім зачепленням) від різниці цих розмірів, коли ширина більше зовнішнього діаметра. Всього досліджено близько 30 конструкцій масляних насосів. Найбільш представницька з цих залежностей, що описує масляні насоси вітчизняних автотракторних двигунів (як бензинових, так і дизельних), має вигляд лінійної функції та характеризується середньою по абсолютній величині відносною похибкою близько 0,015. Інші варіанти залежностей, що представлені у формі квадратичних функцій логарифма різниці зазначених розмірів, відповідають меншим сукупностям масляних насосів дизелів різного призначення (з діаметром циліндрів від 21 до 40 см) і характеризуються цією похибкою близько 0,01 і 0,022. EN: The development of technologies for the production of agricultural products and machinery in Ukraine is taking into account the impact of scientific and technological progress in the leading countries of the world, where industrial methods in agriculture are combined with highly efficient agricultural technologies. Their implementation leads to the renewal of the fleet and accelerates technical progress in agricultural engineering. Based on the analysis of published data on gear oil pumps of transport internal combustion engines, refined variants of the regression of the ratio of the gear width and gear outer diameter of such a pump (with external gearing) against the difference of these dimensions, when the gear width is greater than the outer diameter, are proposed. In total, about 30 designs of oil pumps are investigated. The most representative of these regressions, describing the oil pumps of domestic automotive engines (both gasoline and diesel), has the form of a linear function and is characterized by an average relative error of about 0.015 in absolute value. Other variants of the regression, presented in the form of quadratic functions of the logarithm of the difference of the two gear dimensions, correspond to smaller sets of oil pumps for diesel engines for various purposes (with cylinder diameters from 21 to 40 cm) and are characterized by the error of about 0.01 and 0.022. Regressions of the difference of the two gear dimensions against both of them are analyzed. Plotted experimental points form triangular areas, borders of which are described by linear and quadratic functions. They allow rough prediction of limiting values of the difference when one of the gear dimensions is given. It can be seen that the difference of the two gear dimensions more often increases with increasing any of them. However, reverse trend is also seen when the gear outer diameter is greater than 100 mm. RU: На основе анализа опубликованных сведений о шестерённых масляных насосах транспортных двигателей внутреннего сгорания предложены уточнённые варианты регрессионной зависимости отношения ширины и наружного диаметра такого насоса (с внешним зацеплением) от разности этих размеров, когда ширина больше наружного диаметра. Всего исследованы около 30 конструкций масляных насосов. Наиболее представительная из этих зависимостей, описывающая масляные насосы отечественных автотракторных двигателей (как бензиновых, так и дизельных), имеет вид линейной функции и характеризуется средней по абсолютной величине относительной погрешностью около 0,015. Другие варианты зависимости, представленные в форме квадратичных функций логарифма разности указанных размеров, соответствуют меньшим совокупностям масляных насосов дизелей различного назначения (с диаметром цилиндров от 21 до 40 см) и характеризуются этой погрешностью около 0,01 и 0,022.
Refining parameters of the regression between functions of the main dimensions of gears of oil pumps of vehicle internal combustion engines
Уточнение параметров регрессионной зависимости между функциями основных размеров шестерён масляных насосов транспортных двигателей внутреннего сгорания
Keywords: двигун; масляний насос; шестерня; ширина; зовнішній діаметр; параметр; регресійна залежність; engine; oil pump; gear, width; outer diameter; parameter; regression; двигатель; масляный насос; шестерня; ширина; наружный диаметр; параметр; регрессионная зависимость.